Sandor Type Inequalities for Sugeno Integral with respect to General α, m, r-Convex Functions. (30th December 2015) - Li, Dong-Qing; Cheng, Yu-Hu; Wang, Xue-Song
Abstract : The concept for generalα, m, r -convex functions, as a generalization of convex functions, is introduced. Then, Sandor type inequalities for the Sugeno integral based on this kind of function are established. Our work generalizes the previous results in the literature. Finally, some conclusions and problems for further investigations are given.